Trial by Tabloid: Can Implicit Bias Education Reduce Pretrial Publicity Bias? - Jones, Angela M. (Criminal justice and behavior, 2022)
The Western District of Washington recently developed an educational video to reduce jurors’ implicit biases. Little is known regarding the effectiveness of this proposed remedy to address a range of implicit biases. This study tested whether this educational video reduces pretrial publicity (PTP) bias. A total of 330 undergraduate participants were randomly assigned to read PTP or unrelated articles. An average of 9 days later, they were randomly assigned to watch the educational video prior to viewing a murder trial. Those exposed to PTP were more likely to convict and found the defendant more culpable and less credible. The educational video did not reduce PTP bias. A more tailored debiasing strategy may be needed to overcome the biasing effects of PTP. Differences in legal decisions also emerged depending on whether participants completed the second phase in-person or online, which has implications for future data collection modes.